Analisis Swot Tentang Strategi Pemasaran Dalam Upaya Meningkatkan Kunjungan Pasien Di Klinik Bunda - Subianto, Arie; , Dr. Anton Agus Setiawan, SE, M.Si; , Drs. M Farid Wajdi, M.M, Ph.D (2016)
This research aimed at knowing the variables which are the strength, the weakness, the opportunity, and the threat as well as knowing the marketing strategy implemented by Klinik Bunda based on the position of IE matrix. This research is a joint of qualitative and quantitave researchs based on SWOT analysis and IE matrix using the method of descriptive analysis. The results of the research revealed that basing on the results of analysis on the position of IE matrix, it could be known that the weighted score of internal environment was 4,287 and the weighted score of external environment was 4,000. Based on the weighted scores, the position was in the position of cell I that meant Klinik Bunda was in the position of grow and develop and the strategies that can be implemented are strategies of market penetration, market development, and product development. Hence, the marketing strategy that can be implemented is an aggressive strategy, that is implementing the existing strength and increasing as well as maintaining the existing opportunity.